2008
DOI: 10.3201/eid1410.080102
|View full text |Cite
|
Sign up to set email alerts
|

Endemic and Epidemic Lineages ofEscherichia colithat Cause Urinary Tract Infections

Abstract: Women with urinary tract infections (UTIs) in California, USA (1999USA ( -2001, were infected with closely related or indistinguishable strains of Escherichia coli (clonal groups), which suggests point source dissemination. We compared strains of UTI-causing E. coli in California with strains causing such infections in Montréal, Québec, Canada. Urine specimens from women with community-acquired UTIs in Montréal (2006) were cultured for E. coli. Isolates that caused 256 consecutive episodes of UTI were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
86
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 36 publications
14
86
1
Order By: Relevance
“…Bacterial isolation and identification: 159 E. coli isolates from patients (both sexes) aged 20-55 years with UTIs in Semnan, Iran, during 2015 were isolated according to the protocol described by Manges et al (8) and UTI was defined via the presence of more than two specific clinical symptoms (9). Also 105 E. coli strains from wild birds were isolated through cloacal swabs and feces of the birds in Semnan suburbs (40 strains from captured wild birds and 65 strains from free living wild birds, mainly wild Mallard ducks) and bacterial isolation was carried out according to the protocol of Carrillo-Del Valle et al (10).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial isolation and identification: 159 E. coli isolates from patients (both sexes) aged 20-55 years with UTIs in Semnan, Iran, during 2015 were isolated according to the protocol described by Manges et al (8) and UTI was defined via the presence of more than two specific clinical symptoms (9). Also 105 E. coli strains from wild birds were isolated through cloacal swabs and feces of the birds in Semnan suburbs (40 strains from captured wild birds and 65 strains from free living wild birds, mainly wild Mallard ducks) and bacterial isolation was carried out according to the protocol of Carrillo-Del Valle et al (10).…”
Section: Methodsmentioning
confidence: 99%
“…cause of trimethoprim-sulfamethoxazole-resistant urinary tract infection outbreaks in different communities (12,22,35). Although patients with a urinary source of infection were excluded from the present study, ST69 was identified in three isolates.…”
Section: Vol 48 2010mentioning
confidence: 96%
“…Recent studies have documented the existence of lineages of genetically related E. coli strains, designated clonal groups, which commonly cause urinary tract infections and other extraintestinal infections in various host populations (6,9,12,16,(20)(21)(22)35).…”
mentioning
confidence: 99%
“…Colonization of normal and opportunistic microflora is a main causal agent for UTIs. In the third world, causative factors for UTI include poor hygiene, long time catheterization, uncontrolled sexual intercourse, pregnancy and spermicidal contraception (Manges et al, 2008).…”
Section: Introductionmentioning
confidence: 99%